Le Royaume-Uni : Les conséquences de l’entrée dans la CEE - Marsh, John (Études internationales, 1981)
The brief historical review which opens the article shows that evolutions of the 70''s have les s affected agriculture - already very capitalistic and highly productive - than agricultural policies. The country's entry into the EEC and the need to adapt its agricultural policies to european norms are the main cause of his change. They are at the same time at the center of national debates and form the core of this article which also analyses land, fiscal and marketing policies.